The Impact of Fintech Contributions on Ease of Financial Transaction Management (Study on UNISKA KADIRI Students) - Desi Putri Arika Sari; Nur Rahmawati Ratih; M Wahyudi (LP2M IAIN Palopo, 2026)
The development of financial technology (fintech) has made various financial transactions easier, especially among students. However, this convenience is not necessarily accompanied by good financial transaction management skills. This study aims to determine the influence of fintech's contribution to the ease of managing financial transactions among UNISKA Kediri students. The research method used is a quantitative approach. The fintech contribution variable (X1) has a partial positive and significant effect on the ease of managing financial transactions (Y).